If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + -3) = 5x Reorder the terms: -3(-3 + 2x) = 5x (-3 * -3 + 2x * -3) = 5x (9 + -6x) = 5x Solving 9 + -6x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 9 + -6x + -5x = 5x + -5x Combine like terms: -6x + -5x = -11x 9 + -11x = 5x + -5x Combine like terms: 5x + -5x = 0 9 + -11x = 0 Add '-9' to each side of the equation. 9 + -9 + -11x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -11x = 0 + -9 -11x = 0 + -9 Combine like terms: 0 + -9 = -9 -11x = -9 Divide each side by '-11'. x = 0.8181818182 Simplifying x = 0.8181818182
| 9+3x+x=1 | | 8(7+5n)=256 | | -5x-2=-2x+10 | | 2(4x-2)=2(2x+2) | | -31-3x=-2(6x+2) | | 0.1b+0.6=0.5a | | x-(-88)=64 | | sin(x)+2=3 | | 5a-4=10a-1 | | 72.11*x^2+3490*x-61683.8=0 | | Y=3/5x-6 | | 7/2a=?/10ab^3 | | b/14=27/42 | | 4w+10=6w+13 | | 4/3b-11 | | 3x+0.5=1 | | 10x^2/35x | | 59-3x= | | A=9.87s/260 | | 168=6(1+4a) | | 81/9/3 | | (x^2+1)+(x+-8)=0 | | w^2+4w-1085=0 | | 24/6=X | | 11+r=4(2r+3)-1 | | (x^2+1)=(x-8) | | x+6-8x=3(5-2x)+x | | 1/10b=1 | | 0.1b-0.6=0.5a | | 0.3x-0.4x+6=2 | | a/12=33/36 | | x*.838=(x+50)*.6248 |